2017
DOI: 10.1002/dev.21577
|View full text |Cite
|
Sign up to set email alerts
|

Salivary uric acid and C‐reactive protein associations with hypertension in Midwestern Latino preadolescents and their parents

Abstract: Latino families face increased risk for hypertension. Serum-based uric acid and Creactive protein have been linked to hypertension. However, a paucity of salivary biomarker data exists in this area for Latino families. Using salivary biomarkers enables less invasive options for biomedical and biosocial research, which is especially important among vulnerable populations facing increased health disparities. This study examined the associations between salivary uric (sUA) acid, salivary C-reactive protein (sCRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Jones et al demonstrated that salivary CRP in males was associated with hypertension prevalence and both SBP and DBP levels. 29 Uric acid is another agent correlated with CRP. One of the proposed mechanisms involves stimulating CRP expression in endothelial and smooth muscle cells of blood vessels and activating the IL-1 pathway via high uric acid levels.…”
Section: Arterial Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jones et al demonstrated that salivary CRP in males was associated with hypertension prevalence and both SBP and DBP levels. 29 Uric acid is another agent correlated with CRP. One of the proposed mechanisms involves stimulating CRP expression in endothelial and smooth muscle cells of blood vessels and activating the IL-1 pathway via high uric acid levels.…”
Section: Arterial Hypertensionmentioning
confidence: 99%
“…One of the proposed mechanisms involves stimulating CRP expression in endothelial and smooth muscle cells of blood vessels and activating the IL-1 pathway via high uric acid levels. 29,30 A study by Maciejczyk among children with hypertension found uric acid concentrations in non-stimulated saliva, stimulated saliva, and plasma were significantly higher in children with arterial hypertension compared with controls. 31 However, different results were obtained by Jones et al, who showed that salivary uric acid levels were not associated with BP.…”
Section: Arterial Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The focus on saliva as a non-invasive sample has occurred because of these characteristics (Higashi et al, 2010;Malamud, 2011;Chiappin, et al, 2007). More recent studies revealed that UA is existed in saliva and with the capacity to be measured (Shibasaki et al, 2012;Nunes, Brenzikofer, Macedo, 2011;Jones, Elwazeer, Taylor, 2018;Vakh et al, 2007;Guan, Chu, Ye, 2004). Thus, some researchers found that the amount of UA in plasma is related to that in saliva (Bibi, Green, Nagler, 2008;Deminice, et al, 2010).…”
Section: Development and Validation Of A Simple And Noninvasive Metho...mentioning
confidence: 99%